The Political Causes and Consequences of the Economic Crisis in Greece, 2010-2012 - Sotiropoulos, Dimitri A. (Études helléniques / Hellenic Studies, 2012)
The causes of the economic crisis in Greece, which erupted in 2010, are primarily political and are related to a long-term failure of governance, preceding the crisis. The polarization of political party competition, the extensive politicization of the state administration, the power of strong vested interests, including the interests of state-dependent business entrepreneurs and public sector trade unions, and the dominant populist political culture contributed to the derailment of the Greek economy. In 2010-2012 the consequences of the crisis were both social and political as shown by the spread of unemployment and the rise of the Left and the Far Right. The crisis had consequences beyond Greece’s borders, as it revealed the unpreparedness and incapacity of national governments and international organizations to delimit shifts in international markets and to stabilize the EU and world economy.